1992
DOI: 10.1007/bf00185911
|View full text |Cite
|
Sign up to set email alerts
|

The vertebrate tail bud: three germ layers from one tissue

Abstract: The tail bud of amniote embryos comprises a mass of apparently undifferentiated mesenchymal cells located at the caudal limit of the embryo, representing the remains of Hensen's node and the primitive streak. These cells have the potential to give rise to a variety of different tissues including the posterior or 'secondary' neural tube, the tail gut, and somites and their derivatives. This seemingly homogeneous accumulation of cells therefore has the capacity to differentiate into tissues which in more cranial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(97 citation statements)
references
References 56 publications
(71 reference statements)
2
94
0
1
Order By: Relevance
“…3H-J). Varied expression of sESTs in this region is consistent with the idea that the tail bud does not constitute a blastema, or uniform population of cells (Griffith et al, 1992). Rather, cell fate restrictions have occurred and patterning events are likely to be proceeding due to communication between cells expressing different signaling molecules.…”
Section: Expression Patternssupporting
confidence: 79%
“…3H-J). Varied expression of sESTs in this region is consistent with the idea that the tail bud does not constitute a blastema, or uniform population of cells (Griffith et al, 1992). Rather, cell fate restrictions have occurred and patterning events are likely to be proceeding due to communication between cells expressing different signaling molecules.…”
Section: Expression Patternssupporting
confidence: 79%
“…Wnt-3a was directly involved in the genetic pathway of RA-induced caudal regression. Caudal regression induced by RA was associated with excessive apoptosis of the tail bud (11), which contains progenitor cells for the various tissues of the caudal embryonic region (17,18). It has been shown that Wnt-3a, a gene that encodes a secreted signaling molecule, is indispensable for tail bud development (19).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, they suggested that pluripotent cells of the caudal cell mass may give rise to these tumors through various types of cell-signaling dysfunction. 3,6 The patient described in our case had a cervicothoracic nonterminal myelocystocele containing a teratoma located above the caudal cell mass. It has been postulated that these midline tumors may originate from rests of pluripotent cells at sites of early neural tube closure.…”
Section: 14mentioning
confidence: 82%